2013
DOI: 10.1371/journal.pone.0070058
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biochemical and Gene Expression Analyses of the Antioxidant Activities and Hypocholesterolaemic Properties of Tamarindus indica Fruit Pulp Extract

Abstract: Background Tamarindus indica (T. indica) is a medicinal plant with many biological activities including anti-diabetic, hypolipidaemic and anti-bacterial activities. A recent study demonstrated the hypolipidaemic effect of T. indica fruit pulp in hamsters. However, the biochemical and molecular mechanisms responsible for these effects have not been fully elucidated. Hence, the aims of this study were to evaluate the antioxidant activities and potential hypocholesterolaemic properties of T. indica, using in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 66 publications
3
34
0
3
Order By: Relevance
“…An earlier report in our laboratory revealed that CBP may possess high phenolic content, free radical scavenging activity, and metal chelating and reducing properties, which could exert a beneficial action against pathophysiological alterations caused by the presence of highly reactive radicals and metals . The levels of endogenous antioxidants may also be upregulated by increased expression of the genes encoding the antioxidant enzymes (SOD and CAT) in dietary CBP‐fed type‐2 diabetic rats . In addition, supplementation with 40 g kg −1 CBP in diets of type 2 diabetic rats may have caused a significant ( P < 0.05) elevations of hepatic cytosolic GSTs, which are responsible for the metabolism of numerous xenobiotics and play a major cellular antioxidant role.…”
Section: Discussionmentioning
confidence: 91%
“…An earlier report in our laboratory revealed that CBP may possess high phenolic content, free radical scavenging activity, and metal chelating and reducing properties, which could exert a beneficial action against pathophysiological alterations caused by the presence of highly reactive radicals and metals . The levels of endogenous antioxidants may also be upregulated by increased expression of the genes encoding the antioxidant enzymes (SOD and CAT) in dietary CBP‐fed type‐2 diabetic rats . In addition, supplementation with 40 g kg −1 CBP in diets of type 2 diabetic rats may have caused a significant ( P < 0.05) elevations of hepatic cytosolic GSTs, which are responsible for the metabolism of numerous xenobiotics and play a major cellular antioxidant role.…”
Section: Discussionmentioning
confidence: 91%
“…Hence, the consumption of phenolic-rich fruits has been associated with reduced levels of ROS in animal experiments [55, 56]. Likewise, a high intake of phenolic-rich fruits has been reported to enhance the activities of the antioxidant enzymes [57].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that phenolic compounds from various sources are effective in improving antioxidant enzymes, suggesting their role in the prevention and treatment of oxidative stress-related diseases. Hence, the consumption of phenolic-rich fruits has been associated with reduced levels of ROS in animal experiments [10, 26]. Likewise, a high intake of phenolic-rich fruits has been reported to enhance the activities of the antioxidant enzymes [27].…”
Section: Discussionmentioning
confidence: 99%